2022
DOI: 10.1371/journal.pone.0265133
|View full text |Cite
|
Sign up to set email alerts
|

Tympanoplasty and adenoidectomy in children: Comparison of simultaneous and sequential approaches

Abstract: Background The authors sought to compare simultaneous and sequential tympanoplasty and adenoidectomy surgery in pediatric patients. Methods This retrospective single-center study included 65 children (36 males, 29 females; mean age 9.16 ± 3.82 years; range 3–17 years) requiring both tympanoplasty and adenoidectomy. Simultaneous surgeries were performed on the same day, during single general anesthesia, whereas sequential surgeries were separated at least 12 weeks. The groups were compared with regard to rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…At one, three, and six months after the treatment, the research found that platelet-rich fibrin-assisted temporalis fascia graft survival rates had more telling outcomes than temporalis fascia alone. A meaningful difference between the two groups' hearing threshold gains, however, was not seen (20) . Additionally, our investigation of 60 patients demonstrated that platelet-rich fibrin combined with temporalis fascia resulted in noticeably better outcomes than temporalis fascia alone.…”
Section: Discussionmentioning
confidence: 78%
“…At one, three, and six months after the treatment, the research found that platelet-rich fibrin-assisted temporalis fascia graft survival rates had more telling outcomes than temporalis fascia alone. A meaningful difference between the two groups' hearing threshold gains, however, was not seen (20) . Additionally, our investigation of 60 patients demonstrated that platelet-rich fibrin combined with temporalis fascia resulted in noticeably better outcomes than temporalis fascia alone.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, the combination of adenotonsillectomy with the insertion of grommets was performed in 10.2% of cases. This procedure combination is often employed to address both adenotonsillar hypertrophy and otitis media with effusion, as grommets help to alleviate middle ear fluid accumulation [ 12 , 13 ]. The relatively low frequency of this combination procedure in comparison to adenotonsillectomy alone may reflect variations in patient presentation and otolaryngologists’ clinical decision-making processes.…”
Section: Discussionmentioning
confidence: 99%